2107. Epidemiology and Outcomes Associated with Enterococcal Blood Stream Infection among Abdominal Solid Organ Transplant Recipients. (15th December 2022) - Naqvi, Syed Suhaib; He, Kevin D; Alonso, Carolyn D; Cowan, Vanessa; Stack, Conor; Blair, Barbra M
Abstract: Background: Bloodstream infections (BSIs) account for 18% of bacterial infections in the first year after solid organ transplantation (SOT). Enterococcus is an important cause of nosocomial BSI, accounting for up to 20% of BSIs in this population, with Vancomycin-resistant enterococcus (VRE) posing a particular risk. This study aims to characterize the epidemiology and outcomes of enterococcal BSIs in abdominal SOTs. Methods: A retrospective, single-center, case-control study of adult abdominal organ transplant (kidney transplant (KT), liver transplant (LT), simultaneous liver-kidney transplant (SLK), pancreas transplant, or simultaneous pancreas-kidney transplant) recipients between 01/01/2016 - 07/30/2021 was conducted at Beth Israel Deaconess Medical Center. Subjects were identified and reviewed using the Organ Transplant Tracking Record, their online medical record, and Vigilanz. Subjects with an enterococcal BSI within the first 6 months post-transplant were compared to those with non-enterococcal BSIs in the same period. Results: We identified 26 subjects with enterococcal BSIs and 28 controls with non-enterococcal BSIs (n = 54; 10.2%). Cases were mostly LT recipients (n = 20; 77%) with a median MELD at transplant of 33 (range 14 - 43). Controls included 8 LT recipients (29%), 14 KT recipients (50%), and 6 SLK recipients (21.4%). Groups differed significantly (all p< 0.05) by factors including perioperative transfusion requirements, need for reoperation, and number of interventions post-transplant. Most cases (n = 16; 62%) and 11 controls (39%) had received antibiotics within the month prior to transplant. Cases had a median time of 25.5 days to infection and controls 100.5 days (p < 0.0001) (Figure 1). There were no differences in 1-year mortality (Figure 2) between the groups. E. faecium was the predominant species of Enterococcus (n = 23; 88.5%), with a majority (91.3%) of the isolates being VRE. The VRE rate was 80.8% among cases, 38.9% among all BSIs, and 4.0% among all transplants. Table 1: Demographic, Surgical, Hospitalization, and Antimicrobial Data. Baseline demographic and clinical characteristics of enterococcal BSI cases and non-enterococcal BSI controls are compared, along with transplant characteristics, transfusion requirements, surgical risk factors, hospitalization data, outcomes, and antibiotic exposures. Microbiological and resistance data are also presented. Enterococcal BSIs had lower odds of being a kidney transplant and having CKD or CKD on RRT; they had higher odds of being a liver transplant and having prior immunosuppression, steroid induction alone, reoperations, and macrolide exposure. Enterococcal BSIs had lower KDPIs, higher transfusion requirements, lower cold ischemia times, more procedures, and a shorter time to BSI (Chi-square and Fischer exact tests for categorical variables; Mann-Whitney tests for continuous variables). **Liver and simultaneous liver-kidney transplants; ***Kidney and simultaneous liver-kidney transplants; ****Reoperation within two weeks of primary closure; *****Biopsy proven acute antibody or cellular rejection within 6 months of transplant; ******ERCP stenting compared to IR stenting, among those with biliary complication. BSI – bloodstream infection; CKD – chronic kidney disease; HIV – human immunodeficiency virus; MELD – model of end stage liver disease; KDPI – kidney donor profile index; CMV – cytomegalovirus; pRBC – packed red blood cells; ERCP – endoscopic retrograde cholangiopancreatography; RRT – renal replacement therapy. Figure 1: Time to Bloodstream Infection Probability of BSI-free survival illustrated, with enterococcal BSIs occurring significantly earlier than non-enterococcal BSIs post-transplantation (Kaplan-Meier survival analysis). BSI – bloodstream infection. Figure 2: Mortality Probability of survival, without significant difference between enterococcal and non-enterococcal BSIs. Data censored at one year of follow-up. BSI – bloodstream infection. Conclusion: In our abdominal organ SOTs, enterococcal BSIs occurred early among LT recipients. The high incidence of VRE among E. faecium isolates in this population warrants further investigation into the optimal approach to empiric antimicrobials for bacteremia in the early post-transplant period. Disclosures: Carolyn D. Alonso, MD, Cidara Therapeutics: Advisor/Consultant|Merck: Advisor/Consultant.